Genetic differences among the four Stipa species endangered and protected in Poland - Krzakowa, Maria; Michalak, Marcin; Judek, Maria (Biodiversity: Research and Conservation, 2006)
The distinct character of four species of Stipa genus, S. borysthenica, S. capillata, S. joannis and S. pulcherrima was manifested in the variability of three enzyme systems, including glutamate-oxalacetate transaminase (GOT), esterase (EST) and peroxidase (PX). The studies were conducted on two-month-old seedlings cultured under the same glasshouse conditions, obtained from seeds from the Botanical Gardens collection. Fifteen loci were described, of which eight proved to be polymorphic. The studies included also the complex species of S. pennata and the closely related species of S. tirsa.